STUDI EKSPERIMENTAL BALOK BETON BERTULANG BERSENGKANG TERTUTUP TEGAK DENGAN PENYAMBUNG KAIT DAN LAS - Alivia Andica Puteri; Nor Hidayati; Sri Tudjono; Ilham Nurhuda (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
The development of green construction with the goal of developing the world of constructions are growing. Production process of making steel reinforcement gives negative impact to the environment, such as air pollution, hazardous chemicals and energy waste. This study examines the effectiveness of using reinforcement stirrups in term of their strength and cost. Vertical stirrups have various connection types, such as hooked stirrups and welding connected stirrups. In this study, 6 beam specimens with 3 stirrups variations were prepared, they are 2 beams with hooked stirrups of 135⁰, 2 beams with stirrups welded at the corner and 2 beams with stirrups welded at the center. Eksperimental results of deep beams without compression reinforcements show that the maximum load that can be resisted by both the beams with hooked stirrups and corner welded stirrups are comparable. With regard to the cost, replacement of hooked stirrups with corner welded stirrups can save 5-10% of the total steel used for stirrups.